Domain structure of pseudosymmetric η″-ordered Cu6Sn5 by EBSD analysis. (1st May 2022) - Martin, S.; Winkelmann, A.; Leineweber, A.
Abstract: Cu6 Sn5 is the most prominent intermetallic developing e.g. in solder joints between a Cu-based conductor material and a Sn-based solder. Mechanical reliability issues connected with the intermetallic are a strong driving force to better understand phase-transformation processes involving the intermetallic. In the present work, it is shown for the first time that upon ordering of the Cu-rich Cu6 Sn5 intermetallic, the disordered η phase transforms into the monoclinic η′′ phase with a characteristic twin-domain microstructure consisting of up to 6 different domain orientations per η parent orientation. It is demonstrated how a detailed Kikuchi diffraction pattern analysis in electron backscatter diffraction (EBSD) can be used to investigate the domain microstructure. While the conventional EBSD analysis based on the Hough-transform failed to adequately identify the correct domain orientations, a simulation-based Kikuchi diffraction pattern matching approach is shown to be sensitive to the characteristic positions of those Kikuchi bands which change due to the different monoclinic ordering of the domains. The pattern matching approach explicitly makes use of the subtle intensity contributions from the Kikuchi bands from ordering and that the barely detectable amount of lattice distortion does not have to be the decisive discriminator. Since the ordering can be expected to reduce the ductility of the relatively brittle Cu6 Sn5 intermetallic, the current results provide a basis to reveal more details of possible damage mechanisms of the monoclinic η′′ domain microstructure in comparison with the disordered state. Graphical Abstract: Image, graphical abstract